UPFC based transmission line power load flow control under different operating methods - Lingaswamy, K; Anil Kumar, T; Hari Krishna, G; Shiva Prasad, N (International Journal of Engineering and Technology, 2017)
In this paper the methods to control operation of shunt and series inverters using power flow controller (UPFC) is analyzed with real power flow in power system transmission line. These operation mode using UPFC are executed to reduce Swaying in the control framework transport. The execution about every system may be resolved toward the predefined administrative control. Those arrangement What's more shunt converter working under four separate blending from claiming working modes may be used to ponder An example force framework organize. The line flow in MW oscillation damping is predicated with various modes of operations and verified same with MATLAB/ SIMULINK.